A Platform to Study the Effects of Home Environment on Health and Wellbeing of Older Adults. (17th December 2021) - Baniassadi, Amir; Manor, Brad; Yu, Wanting; Lipsitz, Lewis; Pascual-Leone, Alvaro
Abstract: While older adults' living environment is rarely well-tuned to their specific needs, technological advances provide new opportunities to understand, and ultimately optimize, the relationship between the home environment and health outcomes. We aimed to establish proof-of-concept and feasibility of a platform enabling real-time, high-frequency, and simultaneous monitoring of environment, biological variables, and outcomes related to health and wellbeing in older adults. We recruited 7 participants (6 females, 1 male, aged 78-90, MoCA scores 14–28), installed environmental sensors measuring temperature, humidity, and CO2 inside their homes, provided them with wearables that measure sleep, activity, body temperature, and heart rhythms, and asked them to use a tablet to complete four sets of questionnaires and cognitive tests per day for three consecutive weeks. Environmental sensors collected data with no disruption or complaint from participants. Average compliance with the wearables was 81% (ring) and 60% (watch). All participants preferred the ring due to ease-of-use. Compliance was better in those with higher MoCA scores. Three participants were able to use the tablet successfully and completed 90% of prescribed questionnaires and cognitive tests. Cognitive and/or motor issues prevented the other participants from using the tablet. Exit interviews revealed that participants would prefer to complete a maximum of two sets of daily questionnaires and cognitive tests (five minutes each) in longer-term studies. These results suggest that it is feasible to study the impact of the environment on biological rhythms, cognition, and other outcomes in older adults and provide recommendations for ensuring long-term compliance with the protocol.